Travel photography - Rowe, M. (Bloemfontein: Central University of Technology, Free State, 1995)
without Travel Photography it would be impossible to have an idea of how our ancestors lived, worked and what exotic places they visited. Travel photography can therefore indirectly keep us in touch with our past. In modern society, travel photography is becoming much more popular because many photographers, amateur or professional take images of places that are visited. This dissertation will cover many aspects of travel photography, discussing some of the earlier photographers, as well as technical and praotioal aspects. with travel photography, high ideals can be set. This is the reason why the author has ohosen this topio to discuss. A travel photographer must produoe images that would encourage the viewers to visit these destinations.
Thesis
Keywords: Travel photography; Photography - Study and teaching - South Africa